2019
DOI: 10.1155/2019/3845690
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Destiffening Starts Early after Renal Artery Denervation

Abstract: Introduction. Renal artery denervation (RDN) is a new widely discussed method in treatment of hypertension. Most of the RDN studies assessed BP and arterial changes 3 and 6 months after the procedure, but there is a lack of trials that investigated early changes after RDN. Aim. To investigate aortic stiffness 24-48 hours after the procedure and thus to examine whether RDN might have an early additive value for a cardiovascular risk decline beyond the lowering of blood pressure. Methods. RDN was performed for 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…In our previous study, we also observed a significant reduction in blood pressure and AoPWV that was sustained for up to 12 months after the RDN procedure [ 12 ].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous study, we also observed a significant reduction in blood pressure and AoPWV that was sustained for up to 12 months after the RDN procedure [ 12 ].…”
Section: Introductionmentioning
confidence: 80%
“…A prospective single arm interventional study was conducted between March 2012 and December 2016, and a total of 243 patients with suspected resistant hypertension were referred to university hospital hypertension specialist. They went through a detailed examination according to local hospital protocol, which contained magnetic resonance tomography (MRT) of whole aorta, renal arteries and adrenal glands to rule out secondary hypertension [ 12 ]. If MRT was unable to be performed, a computed tomography scan was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed a rapid, and sustained, drop in cfPWV of 1 m/s after RDN which persisted over a year. This fall in cfPWV preceded and appeared to be independent of changes in office blood pressure [29]. Other studies, however, have found no changes in PWV after RDN [30].…”
Section: Antidiabetic Medicationsmentioning
confidence: 64%
“…RDN lowers BP by reducing systemic vascular resistance and stroke volume in patients with resistant hypertension [46, 47]. Furthermore, RDN may have additional effects on reducing arterial stiffness and cardiovascular risk [48].…”
Section: Discussionmentioning
confidence: 99%